Los espacios de frontera: el locus de la violencia y la disgregación de identidades en Los límites de la noche de Eduardo Antonio Parra (Altre Modernità, 2017)
This paper aims to review how the identity of human barbarism embodied by Eduardo Antonio Parra in the northern topography is transformed in the border spaces, which is transfigured in the locus of violence in the nocturnal wandering of its protagonists, who are subjected to the most varied nuances of social violence that marginalizes, condemns and sometimes annihilates its inhabitants. A disintegration of the bodies of the protagonists is transformed into a disintegration of identities in the spaces in which they transit, a kind of liquid border in which the "limits" allude to a marked individual and social disintegration of northern Mexico. A territory where the inequity of society and the problems generated by violence, insecurity and injustice, lead to a deconstruction of the subject and loss of identity. Parra shows in these stories the decentering of the subject, the nonsense, the presence of the unconscious, the desire, the violence and the alienation. A postmodernity in which only the most intimate bonds become liquid and unstable; in which human contact becomes inconsistent. Three fundamental aspects will be developed in this analysis of Los límites de la noche (Era, 1996): the night as locus of violence in La noche más oscura, the nocturnal animal in the urban barbarism in Como una diosa and the nocturnal voices that transit in the world narrated in El pozo.